A hierarchical biomimetic periosteum combined immunomodulatory and osteogenic functions for bone regeneration. (15th August 2022) - Li, Xiaoming; Yang, Shuang; Wang, Shaochuan; Li, Shidan; Jiang, Hao; Hu, Wenhui; Liu, Ping; Dai, Qijie; Zhang, Bo; Luo, Yanfeng; Dong, Shiwu
Abstract: The periosteum plays an indispensable role in immunomodulation and osteogenesis during bone regeneration. The natural periosteum has a hierarchical structure, in which the outer fibrous layer is composed of fibrous tissue arranged in parallel, while disorganized nanofibers are found in the inner cambium layer. Herein, inspired by the nanostructure/function of the periosteum, we designed a collagen membrane aligned in an oriented manner (CMalig ) to mimic the fibrous layer of the natural periosteum and thereby facilitate the M1-to-M2 phenotypic macrophage transition. The randomly oriented nanofiber membrane (CMrand ) simulated the cambium layer and promoted the osteogenic differentiation of endogenous bone progenitor cells. CMalig induced the M2 polarization of RAW 264.7 cells in vitro, and numerous CD206 + F4/80 + cells were observed at femur defect sites after CMalig treatment. CMrand promoted the osteogenic differentiation of periosteal stem cells and ectopic bone formation in a subcutaneous implantation model. These heterotopic ossifications were also verified in a rat Achilles tendon defect model. The biomimetic periosteum with a hierarchical structure significantly accelerated new bone formation in the rat femur defect model. These results suggest that the hierarchically structured biomimetic periosteum with immunomodulatory and osteogenic functions can be used as an alternative to periosteal autografts. Graphical abstract: Schematic illustration of the preparation of a hierarchically structured biomimetic periosteum for repairing bone defects, in which the outer layer is composing of alignment-oriented collagen membrane (CMalig ), while randomly oriented collagen membrane (CMrand ) in the inner layer. CMalig induced the polarization of macrophages toward the M2 phenotype, and CMrand exhibits osteogenic differentiation and bone biomineralization. Image 1 Highlights: A periosteum structure/function-mimicking collagen membrane was fabricated. The outer face of bionic periosteum facilitates M1-to-M2 transition of macrophages. The inner face promotes osteogenic differentiation and bone biomineralization. The biomimetic periosteum showed superior bone regeneration properties.